Islam dalam Masyarakat Kosmopolit: Relevankah Syariat Islam Aceh untuk Masyarakat Modern? - Shadiqin, Sehat Ihsan (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
This article analyzes the relevance of Islamic lawimplemented in Aceh since 1999 towards a cosmopolitan societydevelopments. The study is based on the assumption that portraitsIslam as a religion that accommodates the development ofterrorism. This assumption is further strengthened by the numberof Islamic radical groups that are involved various acts of terror,both in Indonesia and other places around the world. Therefore,the term âenforcement of Islamic shariaâ becoming a phrase thatraises concerns of many parties and considered as a part ofopening a space for the development of Islamic radicalism.Question will be answered is in what extent Islamic law in Acehrelevant to the cosmopolitan modern society. This question willbe answered by searching the relevant references, criticizing, andinterpreting them. Thus, the author discovered that theimplementation of Islamic law in Aceh does not directly providespace on the birth of Islamic radicalism that could bring upterrorism, but more to the Islamic reduction in normative level,dealing with private issues, and had no social vision. In a largercontext, this kind of implementation of Islamic law will be a badmirror of the Islamic law reality as a whole.